Cover Picture: Target Deconvolution Efforts on Wnt Pathway Screen Reveal Dual Modulation of Oxidative Phosphorylation and SERCA2 (ChemMedChem 12/2017). (21st June 2017) - Casás‐Selves, Matias; Zhang, Andrew X.; Dowling, James E.; Hallén, Stefan; Kawatkar, Aarti; Pace, Nicholas J.; Denz, Christopher R.; Pontz, Timothy; Garahdaghi, Farzin; Cao, Qing; Sabirsh, Alan; Thakur, Kumar; et al.
Abstract : The front cover picture shows the process of photocrosslinking a small molecule functionalized with a diaziridino group to its putative target upon UV irradiation, a critical step in photoaffinity chemical proteomics and target deconvolution. Though not intended to reflect the mode of binding, this depiction shows the photocrosslinking between a 1, 2, 3‐thiadiazole‐5‐carboxamide (TDZ) series with SERCA2, one of the binding partners identified after enrichment and mass spectrometry analysis. Cellular effects observed with the TDZ series are consistent with mitochondrial dysfunction and SERCA engagement and modulation being mechanisms of actions. Front cover art created by Matias Casás‐Selves and Julie Grouleff. More information can be found in the Full Paper by Andrew X. Zhang, et al. onpage 917 in Issue 12, 2017 (DOI:10.1002/cmdc.201700028 ).